The action of selected isothiocyanates on bacterial biofilm prevention and control - Borges, A. (2014)
The activity of two selected isothiocyanates (ITCs), allylisothiocyanate (AITC) and 2-phenylethy-lisothiocyanate (PEITC) was evaluated on the prevention and control of biofilms formed by Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Listeria monocytogenes. In addition, the effect of ITCs was also tested on planktonic cell susceptibility, bacterial motility and adhesion. Biofilm prevention and control were tested using a microtiter plate assay and the effect of ITCs was assessed on biofilm mass and metabolic activity. The minimum bactericidal concentration for E. coli and P. aeruginosa was 1000 μg mL−1 (AITC) and >1000 μg mL−1 (PEITC), for S. aureus and L. monocytogenes was >1000 μg mL−1 (for both ITCs). AITC caused total inhibition of swimming (P. aeruginosa) and swarming (E. coli) motilities. PEITC caused total inhibition of swimming (E. coli, P. aeruginosa and L. monocytogenes) and swarming (E. coli and P. aeruginosa) motilities. Colony spreading of S. aureus was completely inhibited with PEITC. Adhesion assessed in terms of free energy was less favorable when bacteria were exposed to AITC for E. coli and P. aeruginosa and PEITC for P. aeruginosa. Both ITCs had preventive action on biofilm formation and showed a higher potential to reduce the mass of biofilms formed by the Gram-negative bacteria. AITC and PEITC promoted reductions in biofilm activity higher than 60% for all the biofilms tested. The overall study emphasizes the potential of ITCs as emergent products to inhibit bacterial motility and prevent/control biofilms of important human pathogenic bacteria.